Economywide assessment of CSA interventions in building resilient agri-food systems in Rwanda - Aragie, Emerta A.; Thurlow, James; Warner, James; Niyonsingiza, Josue (International Food Policy Research Institute, 2025)
Due to its structural features, the Rwanda’s agri-food system is extremely vulnerable to the risks of climate variability. To accelerate and sustain growth in the food system, increase its resilience to shocks, and improve food security, the Rwandan government incorporated a list of climate-smart agricultural interventions into its updated Fifth Strategic Plan for Agricultural Transformation (PSTA-5) program, with ambitious, explicit targets. This paper assesses the impacts of these CSA interventions on Rwanda’s agri-food system, both with and without climate change, using historical declines in yield within agriculture as a proxy. Results show that modeled CSA practices during the PSTA-5 period (2024/25-2028/29) increase agricultural and overall GDP growth by 4.2 and 1.3 percentage points by the end of the plan period, respectively, with a long-term growth impact that stretches well beyond the plan period mainly owing to the persistent effects of irrigation and terracing. Cumulative agricultural GDP (2024/25-2028/29) would be 2.7 percent higher than the baseline outcome of no such CSA investments. We also find stronger household level effects, mainly in rural areas. Furthermore, a recurrent 1-in-5-year magnitude of climatic shock in Rwanda can cause substantial reductions in agricultural (-7.6 percent) and overall (-2.7 percent) GDP during the PSTA-5 period. The CSA interventions are impactful in minimizing the effects of climate change on the Rwandan economy.